THE CURCUMIN CONTENT OF TEMULAWAK(Curcuma xanthorriza Roxb.) RHIZOME AS AFFECTED BY N, K AND MICRONUTRIENTS B, Fe, Zn - Ellis Nihayati; Tatik Wardiyati; Rurini Retnowati; Soemarno Soemarno (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
A polybag experiment to study the influence of N, K, and micronutrients B, Fe, Zn and the curcumin content in temulawak was conducted in Malang from February – September 2012. Using RBD, 8 treatments (P1 Inseptisol, without fertilizer, P2 Inseptisol 300 urea kg.ha-1, P3 Inseptisol 200 KCl kg.ha-1, P4 Inseptisol 300 kg.ha-1and 200 kg.ha-1 urea and KCl, P5 Alfisol, without fertilizer, P6 Alfisol 300 urea kg.ha-1, P7 Alfisol 200 KCl kg.ha-1, P8 Alfisol 300 kg.ha-1 and 200 kg.ha-1 urea and KCl in 3 replications. The micronutrients in vitro applied RCD by 4 treatments (MS medium, MS without B, Fe and Zn) in 10 replications. The results of experiment showed that dry weight of rhizome per plant in Inseptisol and Alfisol is 30.98 and 9.75 g, content of curcumin 6 month after planting was 3.60 and 4.72%. The highest rhizome weight of 8 months after planting was a combination of N and K of Inseptisol (48.28) and Alfisol (35.75 g per plant).The highest content of curcumin 6 months after planting was on Alfisol (7.99%) and Inseptisol (6.7%) by 200 KCl kg.ha-1.The curcumin content in complete media was higher than that without B, Fe and Zn i.e. 6.26 compared with 1.86–2.39%. Keywords : temulawak (Curcuma xanthorriza Roxb. Synm. Curcuma javanica), N, K, B, Fe, Zn, curcumin content